Encryption wars early battles. - Caloyannides, M.A.
The rise of the so called information economy, borne along by proliferating computers, sprawling telecommunications, and the Internet, has radically transformed how people do business, govern, entertain themselves, and converse with friends and family. Private documents that in the past would have been committed to paper and hand-delivered or stowed under lock and key are now routinely created, sent, and stored electronically. But the very things that allow such speed and ease of communication have also made it far more difficult to ensure one's privacy. In an electronic age, an interloper can intercept and alter messages far more easily now than when face-to-face exchanges were the norm. Mounting concern over the new threats to privacy and security has led to widespread adoption of cryptography. The first part of this two-part article reviews the encryption techniques now available worldwide and discusses the legal campaigns that governments have mounted in response, including the changes proposed to US export laws
Keywords: Internet; US export laws; Computers; Cryptography; Electronic document delivery; Electronic message interception; Encryption techniques; Information economy; Legal campaigns; Private documents; Public-key encryption; Symmetric encryption; Telecommunications